Identification and Expression Analysis of the Complete Family of Zebrafish pkd Genes - England, Samantha J.; Campbell, Paul C.; Banerjee, Santanu; Swanson, Annika J.; Lewis, Katharine E. (Frontiers in Cell and Developmental Biology, 2017)
Polycystic kidney disease (PKD) proteins are trans-membrane proteins that have crucial roles in many aspects of vertebrate development and physiology, including the development of many organs as well as left-right patterning and taste. They can be divided into structurally-distinct PKD1-like and PKD2-like proteins and usually one PKD1-like protein forms a heteromeric polycystin complex with a PKD2-like protein. For example, PKD1 forms a complex with PKD2 and mutations in either of these proteins cause Autosomal Dominant Polycystic Kidney Disease (ADPKD), which is the most frequent potentially-lethal single-gene disorder in humans. Here we identify the complete family of pkd genes in zebrafish and other teleosts. We describe the genomic locations and sequences of all seven genes: pkd1, pkd1b, pkd1l1, pkd1l2a, pkd1l2b, pkd2 and pkd2l1. pkd1l2a/pkd1l2b are likely to be ohnologs of pkd1l2, preserved from the whole genome duplication that occurred at the base of the teleosts. However, in contrast to mammals and cartilaginous and holostei fish, teleosts lack pkd2l2 and pkdrej genes, suggesting that these have been lost in the teleost lineage. In addition, teleost, and holostei fish have only a partial pkd1l3 sequence, suggesting that this gene may be in the process of being lost in the ray-finned fish lineage. We also provide the first comprehensive description of the expression of zebrafish pkd genes during development. In most structures we detect expression of one pkd1-like gene and one pkd2-like gene, consistent with these genes encoding a heteromeric protein complex. For example, we found that pkd2 and pkd1l1 are expressed in kupffer’s vesicle and pkd1 and pkd2 are expressed in the developing pronephros. In the spinal cord, we show that pkd1l2a and pkd2l1 are co-expressed in KA cells. We also identify potential co-expression of pkd1b and pkd2 in the floor-plate. Interestingly, and in contrast to mouse, we observe expression of all seven pkd genes in regions that may correspond to taste receptors. Taken together, these results provide a crucial catalogue of pkd genes in an important model system for elucidating cell and developmental processes and modeling human diseases and the most comprehensive analysis of embryonic pkd gene expression in any vertebrate.